Re-implant of the right coronary artery: a surgical technique for the treatment of ostial lesions - Bongiovani,Hércules Lisboa (2002)
Previously described surgical treatment for ostial coronary artery stenosis relied on either venous or arterial bypasses or ostial patch angioplasty. These surgical procedures are performed with bovine pericardium, saphenous vein or internal thoracic artery. We describe a technique of right coronary artery re-implantation into the aorta. The procedure was performed in four patients with right coronary artery ostial stenosis along with other left coronary artery lesions.